In the face of a shift of paradigm in Mercusor: A summary of its last twenty years - Castañeda Oré, Priscila (2019)
Objective: This document includes the bibliographic review of The Southern Common Market’s (Mercosur) intramural and extramural political and commercial relations both in relation to its members and in relation to its commercial partners from its genesis to the end of the government of Dilma Roussef and Cristina Kirchner. In that sense, an attempt will be made to demonstrate how profitable it could have been that both Argentina and the other block members ascribed to the geopolitical strategy under the bloc's biggest partner Brazil who ruled its political-commercial strategy with the bloc from its beginning until the conclusion of the afore-mentioned government. Method: A descriptive analysis based on a bibliographic review aimed at analyzing the political and commercial strategies adopted by the member countries of Mercosur. Additionally, since the economic policy of Brazil and to a lesser extent the economic policy of Argentina constitute the main economies of the reference integration scheme an examination of both was preeminently considered. Results: The results show that the strategy adopted by Brazil, a typical global trader, who prioritized its national interest had positive effects not only at the commercial level, but also at the political level while the other countries of the bloc based their strategies on poorly defined and unstable economic interests, according to the current administration, whose implications weakened cooperation. Conclusion: It is claimed in the present work that the failure to follow the Brazilian strategy on the part of the smaller Mercosur members constituted an economic and political error.